Attitudes towards mode choice in Switzerland. - Atasoy, Bilge; Glerum, Aurélie; Bierlaire, Michel (Routledge, 2013)
Der Beitrag stellt Modelle vor, die mittels latenter Klassen und Variablen, die Einstellungen von Verkehrsteilnehmern in Verkehrsmittelwahluntersuchungen integrieren und damit bessere Ergebnisse liefern. Die latenten Klassen und Variablen, die als signifikante Größen im Verkehrsverhalten identifiziert werden, wurden mithilfe psychometrischer Indikatoren gewonnen. Für die empirische Untersuchung wurden Daten qualitativer (Interviews) und quantitativer Datenerhebungen (Befragung über das Mobilitätsverhalten Bewohner suburbaner Räume in der Schweiz) ausgewertet.

We integrate latent attitudes of the individuals into a transport mode choice model through latent variable and latent class models. Psychometric indicators are used to measure these attitudes. The aim of the inclusion of attitudes is to better understand the underlying choice preferences of travelers and therefore increase the forecasting power of the choice model. We first present an integrated choice and latent variable model, where we include attitudes towards public transport and environmental issues, explaining the utility of public transport. Secondly, we present an integrated choice and latent class model, where we identify two segments of individuals having different sensibilities to the attributes of the alternatives, resulting from their individual characteristics. The calibration of these types of advanced models on our sample has demonstrated the importance of attitudinal variables in the characterization of heterogeneity of mode preferences within the population.
Keywords: Verkehr; Verkehrswissenschaft; Verkehrsmittelwahl; Verkehrsverhalten; Modell